Traditional way of learning Ayurveda and practising it : a dialogue with Vaidya Bhaskarbhai Hardikar - Dixit, Mukund R.; Verma, Sanjay; Patel, Amit (London : Indian Institute of Management, Ahmedabad, 2014)
Vaidya Bharskarbhai Hardikar is an Ayurveda practitioner trained through the traditional system of education. This interview with Hardikar reveals his personal process of learning Ayurveda, and how he applies it in practice. This case provides an excellent demonstration of different methods of knowledge acquisition and management, as Hardikar learned his skills through a variety of diverse methods.
Originally Published InDixit, M., Verma, S., & Patel, A. (2014). Traditional way of learning Ayurveda and practising it: A dialogue with Vaidya Bhaskarbhai Hardikar. Ahmedabad, IN: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Hardikar, Vaidya Bhaskarbhai; Medicine, Ayurvedic -- Case studies